The Identification of Dual T-Cell and B-Cell Epitopes Within Viral Proteins Utilizing a Comprehensive Peptide Array Approach - Binghang Liu; Muqun Bai; Fei Zheng; Mingchen Yan; Enen Huang; Jie Wen; Yingrui Li; Jun Wang (Vaccines)
Background/Objectives: The development of vaccines that elicit both T-cell and B-cell responses is crucial for effective immunity against pathogens. This study introduces a novel approach to identify precise epitope peptides within viral proteins that can stimulate both arms of the adaptive immune response, using Porcine Parvovirus (PPV) as a model. Methods: Mice were infected with PPV, and a peptide array was utilized to detect IgG signals in their sera. This approach facilitated the assessment of the immunogenicity of the PPV proteome, leading to the identification of 14 potential epitope candidates. These candidates were then used to immunize additional mice, and their ability to induce T-cell and B-cell responses was evaluated. Results: The immunization experiments identified an optimal peptide, P6, which robustly activated both T cells and B cells. Further analysis of the sub-regions of this peptide confirmed P6 as the most potent inducer of immune responses. The anticipated epitope was detected in mice immunized with P6, highlighting the efficacy of our method in identifying epitopes that engage both T cells and B cells. Conclusions: This study presents a novel strategy for the identification of dual T-cell and B-cell epitopes by directly evaluating the immunoreactivity of antibodies in serum. This finding holds significant promise for the advancement of epitope-based vaccines.